2015
DOI: 10.1007/s00737-015-0573-5
|View full text |Cite
|
Sign up to set email alerts
|

Childhood maltreatment and pre-pregnancy obesity: a comparison of obese, overweight, and normal weight pregnant women

Abstract: Pre-pregnancy overweight and obesity is associated with poor health outcomes for the mother and the child. General population studies suggest that childhood maltreatment is associated with obesity in adulthood. The aim of our study was to examine the association between pre-pregnancy overweight and obesity and a history of childhood abuse or neglect including different stages of severity of abuse and neglect. Three hundred twenty-six normal weight, overweight, or obese pregnant women reported demographic data,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 63 publications
1
13
0
Order By: Relevance
“…Based on a model of psychoneuroimmunology during pregnancy (Christian, 2015) and existing literature, the potential mediating role of pre-pregnancy body composition in the observed associations between trauma exposure and inflammation was of interest. Prior studies have linked childhood abuse and neglect with pre-pregnancy overweight and obesity (Hollingsworth, Callaway, Duhig, Matheson, & Scott, 2012; Nagl, Steinig, Klinitzke, Stepan, & Kersting, 2016; Ranchod et al, 2016). Further, data from 326 non-pregnant women demonstrated that observed associations between child abuse and neglect exposure with elevated serum CRP were mediated by BMI (Matthews, et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Based on a model of psychoneuroimmunology during pregnancy (Christian, 2015) and existing literature, the potential mediating role of pre-pregnancy body composition in the observed associations between trauma exposure and inflammation was of interest. Prior studies have linked childhood abuse and neglect with pre-pregnancy overweight and obesity (Hollingsworth, Callaway, Duhig, Matheson, & Scott, 2012; Nagl, Steinig, Klinitzke, Stepan, & Kersting, 2016; Ranchod et al, 2016). Further, data from 326 non-pregnant women demonstrated that observed associations between child abuse and neglect exposure with elevated serum CRP were mediated by BMI (Matthews, et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, our results are consistent with other findings of only physical abuse being associated with adult obesity and that other ACE exposures may confer different effects than physical abuse. [6][7][8]12 The prevalence of physical abuse in this study was similar to that among women in the BRFSS, but the prevalences of household mental illness and alcoholism were lower by 8.1 and 4.6 percentage points, respectively, suggesting that our study group may have underreported these exposures 36 ; therefore, we cannot confidently rule out their importance. We were also unable to assess other types of abuse and neglect, which could confound the association between physical abuse and early childhood obesity or be independent risk factors.…”
Section: Discussionmentioning
confidence: 43%
“…4,5 In numerous additional studies, researchers have also found adverse childhood experiences (ACE) to be associated with obesity in adulthood. [6][7][8][9] Most recently, adversity in childhood has been associated with high prepregnancy BMI and excessive weight gain during pregnancy [10][11][12] as well as offspring obesity. 13 We sought to bridge the bodies of evidence connecting childhood adversity with maternal obesity and maternal obesity with child obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Less is known about these associations during pregnancy. We are aware of only two studies with a focus on associations between different types of childhood maltreatment and obesity among pregnant women [ 34 , 35 ] consistently suggesting an increased risk of pre-pregnancy obesity among women with a history of childhood physical abuse. Findings for emotional abuse are inconsistent with one study suggesting a positive association [ 34 ] and the other suggesting no association [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…We are aware of only two studies with a focus on associations between different types of childhood maltreatment and obesity among pregnant women [ 34 , 35 ] consistently suggesting an increased risk of pre-pregnancy obesity among women with a history of childhood physical abuse. Findings for emotional abuse are inconsistent with one study suggesting a positive association [ 34 ] and the other suggesting no association [ 35 ]. Particularly childhood abuse has also been found to be associated with ante- and postnatal depression, anxiety and generalized anxiety disorder among pregnant women [ 20 , 30 , 36 38 ].…”
Section: Introductionmentioning
confidence: 99%